Salivary IgA against sporozoite-specific embryogenesis-related protein (TgERP) in the study of horizontally transmitted toxoplasmosis via T. gondii oocysts in endemic settings. Issue 12 (12th May 2016) - MANGIAVACCHI, B. M.; VIEIRA, F. P.; BAHIA-OLIVEIRA, L. M. G.; HILL, D.
SUMMARY: The aim of this study was to contribute to the better understanding of the relative epidemiological importance of different modes of infection with respect to horizontal transmission of Toxoplasma gondii in endemic settings. We investigated the prevalence of salivary IgA against a sporozoite-specific embryogenesis-related protein (TgERP) in a highly endemic area for toxoplasmosis in Brazil in order to pinpoint parasite transmission via oocysts. Prevalence calculated by salivary IgA specific to TgERP was compared to the prevalence calculated by serum IgG against both TgERP and tachyzoites (in conventional serological tests). Prevalence calculated by different serological and salivary parameters varied in the studied age groups. However, for the 15–21 years age group, values for T. gondii prevalence estimated by conventional serological tests and by anti-TgERP salivary IgA were similar; i.e. 68·7% and 66·6% or 66·7%, respectively, using two different cut-off parameters for salivary IgA anti-TgERP. Furthermore, salivary IgA anti-TgERP for this age group presented the highest specificity (93·33%), sensitivity (93·94%), and likelihood (14·09) compared to all the other age groups. These data demonstrate the importance of age for salivary IgA investigation against TgERP to estimate the mode of T. gondii transmission in endemic settings.